PENGARUH EFEKTIVITAS, HEDONIS, KEMANFAATAN, DAN KEPERCAYAAN TERHADAP MINAT MAHASISWA UNIVERSITAS NEGERI MALANG DALAM MENGGUNAKAN LAYANAN SHOPEEPAY: PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL - Taruni Risla Hanifah; Imam Mukhlis (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2022)
Financial inclusion is one of the indicators used in knowing the development of the financial system in a country. Financial Technology can be used in overcoming the problem of financial inclusion because it can create access to financial services easily and improve the system to be more efficient in addition to the financial technology that develops in people's lives that encourages a cashless society, namely by creating electronic money innovations contained in an application platform called e-wallet. ShopeePay is an e-wallet that is popular among the public today. Therefore, researchers use variables of effectiveness, hedonistic, usefulness, and trust as independent variables and the interest of students of State University of Malang in using ShopeePay services as dependent variables. Researchers use variables of effectiveness, hedonistic, usefulness, and trust because according to the Technology Acceptance Model the variable is a factor that influences an individual's interest in using technology. This study used quantitative data with data collection methods in the form of questionnaires with a Linkert scale. The result of this study is that the variables of effectiveness, hedonics, and usefulness have a significant influence on the interest in using ShopeePay services. While the trust variable does not have a significant influence on the interest in using ShopeePay services